메탄발효와 퇴비화 공정이 연계된 가축분뇨 처리시설에서 발생되는 악취물질 특성 조사 - 고한종; 김기연; 김현태; 고문석; 히구치 다카시; 우메다 미키오; Ko, Han Jong; Kim, Ki Youn; Kim, Hyeon Tae; Ko, Moon Seok; Higuchi, Takasi; Umeda, Mikio (Journal of animal science and technology, 2008)
Odor management is significantly concerned with sustainable livestock production because odor nuisance is a primary cause for complaint to neighbors. This study was conducted to measure the concentration of odorous compounds, odor intensity, and odor offensiveness at unit process in animal waste treatment facility combined composting and methane fermentation process by an instrumental analysis and direct olfactory method. Ammonia, sulfur-containing compounds, and volatile fatty acid were analyzed at each process units and boundary area in summer and winter, respectively. Higher concentration of odorants occurred in the summer than in the winter due to high ambient temperature. The maximum concentration of odorants was detected in composting pile when mixed manure was being turned followed by inlet, curing, outlet, and screen & packing process. Highest concentration of detected odorous compounds was ammonia ranging from 3.4 to 224.7 ppm. Among the sulfur-containing compounds measured, hydrogen sulfide was a maximum level of 2.3 ppm and most of them exceeded reported odor detection thresholds. Acetic acid was the largest proportion of VFA generated, reaching a maximum of 51 to 89%, followed by propionic and butyric acid at 1.9 to 35% and 1.8 to 15%, respectively. Malodor assessment by a human panel appeared a similar tendency in instrumental analysis data. Odor quotient for predicting major odor-causing compounds was calculated by dividing concentrations measured in process units by odor detection thresholds. In the composting process, hydrogen sulfide, ammonia, dimethyl sulfide, and methyl mercaptan were deeply associated with odor-causing compounds, while the major malodor compounds in the inlet process were methyl mercaptan, hydrogen sulfide, and butyric acid. 악취는　이웃주민들로　하여금　민원을　유발시키는　주요　원인이기　때문에　악취관리는　지속가능한 축산과　매우 밀접한 관계가 있다. 본 연구는 메탄발효와 퇴비화 공정이 연계된 가축분뇨 처리시설에서 각 공정별로 기기분석과 직접 관능법을 병행하여 악취 물질의 농도, 악취 강도 및 악취 불쾌도를 측정하고자 수행하였으며, 하계와 동계로 구분하여 처리 공정과 부지경계선에서 각각 암모니아, 황화합물 및 휘발성 저급지방산의 농도를 분석하였다. 높은 외기온에 기인하여 하계의 악취농도가 동계보다 높은 것으로 나타났다. 공정별로는 혼합된 분뇨를 교반하는 퇴비화 공정에서 악취 농도가 가장 높게 검출되었으며, 분뇨 투입조, 퇴비 후숙조, 분뇨 유출조 및 퇴비 선별과 포장 공정의 순으로 악취 농도가 낮았다. 검출된 악취 물질 중 가장 높은 농도는 암모니아로 3.4에서 224.7 ppm의 농도 범위로 분석되었다. 황화합물 중에서는 황화수소가 가장 높은 농도인 2.3 ppm인 것으로 분석되었으며, 대부분의 황화합물 농도가 기존에 보고된 최소감지한계농도를 초과하는 것으로 측정되었다. 또한 아세트산은 휘발성 저급지방산 가운데 51에서 89%로 가장 놓은 비율을 차지하고 있으며, 다음으로는 프로피온산과 부트르산이 각각 1.9에서 35% 및 1.8에서 15%의 비율을 보이는 것으로 나타났다. 처리공정에서 발생되는 주요 악취원인 물질을 예측하고자 각각의 공정에서 측정된 악취물질의 농도를 최소감지한계농도로 나누어 악취농도지수를 계산하였다. 그 결과 퇴비화 공정에서는 황화수소, 암모니아, 황화메틸 및 메틸머캅탄이 악취원인 물질로 밀접한 연관이 있는 것으로 나타났으며, 분뇨 투입조에서는 황화수소, 메틸머캅탄 및 부트르산이 주요 악취물질인 것으로 나타났다.